Super colour gamut LCD technology with laser illumination - Lim, Wei Rong (2019)
This Final Year Project aims to create a white light from laser diodes of three primary colours of red, green and blue. The purpose is to create a possible alternative white light for the backlight unit of a Super Colour Gamut Laser TV for enhanced visual display. Study shows that increase in pixel resolution of a TV does not effectively improve image quality. On the other hand, due to the characteristic of having narrow linewidth, lasers can generate true colour of accuracy, expanding the coverage of colour gamut compared to existing backlights. Considerations are made in choosing the hardware components and an electrical circuit design is conceived for experimentation. A colour test is conducted by converging laser illuminations and results shown that converging light emitted from laser diodes of red, green and blue are not only able to produce a visible white light, but also other visible light of yellow, magenta and cyan, colours within the super colour gamut.